Tradisi Ngayah Pada Masyarakat Bali - Mubarak Dahlan (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
Ngayah tradition is rooted in religion and has a purpose, but it also instills social and environmental obligations in addition to ritual qualities, as it encourages individuals to gather and interact with each other, ngayah can be seen as a community unifying activity. The main purpose of these ngayah events is to ensure that an event, usually a religious event and especially an important event, runs successfully. There are three forms of ngayah that can be recognized in daily life in relation to its application including Ngayah meaning loyalty and commitment, Ngayah with a focus on sociocultural activities, Ngayah related to regional religion. The presence of modernization in the midst of people's lives causes major changes in all aspects of people's lives. Along with the progress of the way of life of the community itself, the ngayah system used in religious rituals by the Balinese Hindu community has also developed.